2003
DOI: 10.1007/s00213-003-1448-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sertraline on autonomic and cognitive functions in healthy volunteers

Abstract: Cognitive and psychomotor performance are not altered in healthy humans receiving multiple dosing with sertraline. The observed decreases in heart rate and SCL may be due to a sympatho-inhibitory effect of sertraline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 34 publications
2
79
0
2
Order By: Relevance
“…Siepmann et al [53] investigated the effects of sertraline on autonomic and cognitive function in a randomized, placebo controlled, crossover study. They gave 12 healthy male volunteers 50 mg of sertraline and placebo, each for 14 days (with a 14-day washout period in between).…”
Section: Discussionmentioning
confidence: 99%
“…Siepmann et al [53] investigated the effects of sertraline on autonomic and cognitive function in a randomized, placebo controlled, crossover study. They gave 12 healthy male volunteers 50 mg of sertraline and placebo, each for 14 days (with a 14-day washout period in between).…”
Section: Discussionmentioning
confidence: 99%
“…The flow reduction could occur through the serotonin receptor action presented at the peripheric microcirculation (Hunter & Wilson, 1995;Siepmann et al, 2003). According to Schubert & Izutsu (1987), the salivary flow can be affected by drugs through alteration of the blood flow to the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the introduction of a heterogeneous group of compounds (to which venlafaxine belongs), the atypical antidepressants. In practice, the most recent drugs may definitively be superior to the tricyclic drugs in terms of side effects and acute toxicity, but they have not been shown to have a faster action or be more effective (Goldstein & Goodnick, 1998;Siepmann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in healthy volunteers have been conducted to assess the effects of SSRIs on memory specifically but these studies have shown controversial results. Subchronic administration of sertraline produced no effects on memory compared to placebo (Schmitt et al, 2001;Siepmann et al, 2003) but subchronic administration of paroxetine did impair delayed recall on a memory task (Schmitt et al, 2001). An acute dose of the SSRI fluvoxamine, 50 and 100 mg, produced no effect on memory compared to placebo (Fairweather et al, 1996).…”
Section: Introductionmentioning
confidence: 96%